2020
DOI: 10.3390/nu12051279
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus plantarum 299v on Iron Status and Physical Performance in Female Iron-Deficient Athletes: A Randomized Controlled Trial

Abstract: Iron is an essential micronutrient for oxygen transport and mitochondrial metabolism and is critical for physical performance. Compromised iron stores are more commonly found among athletes, and females are especially at risk. Iron deficiency is generally treated using oral iron supplements. However, only a small proportion of ingested iron is absorbed, necessitating higher intakes, which may result in adverse side effects, reduced compliance, and inefficient repletion of iron stores. The probiotic strain Lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 57 publications
4
68
0
Order By: Relevance
“…All fourteen clinical trials were published in journals between the years 2000 and 2020. Studies were conducted in Austria [ 42 , 43 , 44 ], Indonesia [ 45 , 46 ], USA [ 47 ], India [ 48 ], Sweden [ 49 ], Italy [ 50 ], Egypt [ 51 ], Finland [ 16 ], Brazil [ 28 ], Serbia [ 52 ], and one was a multinational study [ 32 ]. Study design across the 14 included studies varied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All fourteen clinical trials were published in journals between the years 2000 and 2020. Studies were conducted in Austria [ 42 , 43 , 44 ], Indonesia [ 45 , 46 ], USA [ 47 ], India [ 48 ], Sweden [ 49 ], Italy [ 50 ], Egypt [ 51 ], Finland [ 16 ], Brazil [ 28 ], Serbia [ 52 ], and one was a multinational study [ 32 ]. Study design across the 14 included studies varied.…”
Section: Resultsmentioning
confidence: 99%
“…Study design across the 14 included studies varied. Four studies were randomized double-blind placebo-controlled trials [ 45 , 46 , 49 , 50 ], two others used a cross-over design [ 16 , 48 ], one was an open-label, randomized, multicenter study [ 32 ], and four randomized trials did not report blinding [ 43 , 44 , 47 , 51 ]. Three studies were nonrandomized trials [ 28 , 42 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the absorption of iron could be a strategy for improving iron status and avoid the use of traditional high-dose iron supplements and thereby adverse side effects. In a recent double blind, 12 week randomized control trial in nonanemic female athletes with low-iron stores receiving a daily supplement of 20 mg of ferrous fumarate, L. plantarum 299v increased plasma ferritin (iron status), in those with ferritin levels above 20 μg/l at baseline compared with control [ 22 ▪ ]. Significantly, those with ferritin levels below 20 μg/l did not differ from each other in terms of the ferritin response (increase).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics can even be helpful in treating recurring urinary tract infections (UTIs) in some women [ 162 ]. A recent study relevant to females, demonstrated an improvement in iron levels and absorption when 20 mg of iron (ferrous-fumarate) was combined with lactobaccilus plantarum 299v (LP299V, 10 10 CFU), suggesting this probiotic strain may help improve iron levels [ 163 ]. Probiotics should be chosen based on strain and desired outcome; strains may vary for women compared to men [ 164 , 165 ].…”
Section: Dietary Supplementsmentioning
confidence: 99%